Extrusion- and Pultrusion-Compounded Carbon Fibre Reinforced Polyamide 6,6 Composites : Impact Properties of Injection Moulded Specimens - Hassan, Aziz; Yahya, Rosiyah; A. Rahman, M. Tahir; Yahaya, A. Hamid (Malaysian Journal of Science, 2003)
Processing of discontinuous fibre reinforced thermoplastic composites normally involves compounding and moulding, whereby fibre breakage problem could not be avoided. Pultrusion compounding technique has proven to improve tensile and fibre length characteristics of injection moulded specimens over extrusion technique. In this work, both pultrusion and extrusion techniques were employed to compound carbon fibre with polyamide 6,6 matrix, followed by injection moulding and testing for their impact properties. The values of $G_c$ and $K_c$ are increased with increase in fibre volume fraction. These values are also increased with increase in fibre length at lower fibre loadings ($V_f$ of 0.20 and 0.21) but decreased with an increase in fibre length at higher fibre loadings ($V_f$ of 0.31 and 0.32).